Differential phosphatidic acid metabolism in barley leaves and roots induced by chilling temperature - Peppino Margutti, Micaela Yesica (2018)
Phosphatidic acid (PA) is an important bioactive lipid that mediates chilling responses in barley. Modifications in the lipid composition of cellular membranes during chilling are essential to maintain their integrity and fluidity. First, we investigated the molecular species of PA present in leaves and roots by ESI-MS/MS, to evaluate the modifications that occur in response to chilling. We demonstrated that PA pools in leaves differ from PA fatty acid composition in roots. Compared with plants grown at 25 °C, the short-term and long-term chilling for 3 h and 36 h at 4 °C not produced significant changes in PA molecular species. The endogenous DAG and PA phosphorylation by in vitro DAG and PA kinase activities showed higher activity in leaves compared with that in root, and they showed contrasting responses to chilling. Similarly, PA removal by phosphatidate phosphohydrolase was tested, showing that this activity was specifically increased in response to chilling in roots. The findings presented here may be helpful to understand how the PA signal is modulated between tissues, and may serve to highlight the importance of knowing the basal PA pools in different plant organs.